Odpowiedzi

2010-03-11T18:46:03+01:00
A)-(2x-1)=4
-2x+1=4
-2x=3 |: (-2)
x=-1,5
b)2(x+1)=x
2x+2=x
x=-2
c)2t-(3t+1)=6
2t-3t-1=6
-t=7 |: (-1)
t=7
d)-(4+x)=2(3-x)
-4-x=6-2x
-10=-x |:(-1)
x=10
e)3(y+6)-y=2(y+9)
3y+18-y=2y+18
0=0
f)(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=20 |:(-5)
x=-4
Najlepsza Odpowiedź!
2010-03-11T19:10:04+01:00
A.
-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/:-2
x=-3/2
spr.-(2*(-3/2) - 1)=4
-(-3-1)=4
-(-4)=4
4=4
b.
2(x+1)=x
2x+2=x
2x-x=-2
x=-2
spr. 2(-2+1)=-2
2*(-1)=-2
-2=-2

c.
2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7/*-1
t=-7
spr. 2*(-7)-[3*(-7)+1]=6
-14-(-21+1)=6
-14-(-20)=6
-14+20=6
6=6

d.
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
spr. -(4+10)=2(3-10)
-14=2*(-7)
-14=-14

e.
3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y-2y=18-18
0=0

f.
(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=3+10+7
-5x=20/:-5
x=-4
spr. (-4-7)-2[3*(-4)+5]=3
-11-2(-12+5)=3
-11-2*(-7)=3
-11+14=3
3=3

g.
0,1x+0,2=-0,3
0,1x=-0,3-0,2
0,1x=-0,5/:0,1
x=-5
spr. 0,1*(-5)+0,2=-0,3
-0,5+0,2=-0,3
-0,3=-0,3

h.
0,25x+0,=0,35

i.
1-0,2x=-0,3x
1=-0,3x+0,2x
1=-0,1x/:-0,1
x=-10
spr. 1-0,2*(-10)=-0,3*(-10)
1+2=3
3=3

j.
0,01x-1=0,1x-0,1
0,01x-0,1x=-0,1+1
-0,09x=0,9/:-0,09
x=-10
spr. 0,01*(-10)-1=0,1*(-10)-0,1
-0,1-1=-1-0,1
-1,1=-1,1
1 5 1